Firn Permeability and Density at WAIS Divide - Albert, Mary R. (IEDA: US Antarctic Program Data Center, 2015)
This data set contains laboratory measurements of the density and permeability made from firn cores from the lock-in zone through pore close-off at the WAIS Divide and Megadunes sites.